Trajectories of reconstruction and negotiation of relationships in displacement: Intimacy among Syrian families in Lebanon - Tuzi, Irene (2023)
The article explores the impact of forced migration on gender relations among Syrian families in Lebanon and aims to analyze some of the transformations that have affected the intimate relationships of refugee families. It focuses in particular on how women and men in displacement reconstruct intimacy using resilience as a dimension of agency. The research questions the article answers are: what is the impact of forced migration on intimacy? How are intimate relationships reconstructed in forced migration? Based on an ethnographic study carried out in Lebanon between 2017 and 2019, this article proposes an interpretation of the trajectories of reconstruction and negotiation of gender relations through the concept of resilience. The results of this study show that resilience as a dimension of agency enables the practice of active and creative techniques of negotiating relationships and reconstructing intimacy in forced migration.